Distribution of affordable housing in Yinchuan, China - Zhang, Tao (2012)
Affordable housing is built with public assistances and public land in Yinchuan. It aims to provide an accommodation with security and stability to the urban poor and help them overcome disadvantages and live as a human being with dignity. It is absolutely unacceptable that the ineligible occupy affordable housing and obtain welfare benefits. The affordable housing fraud deprives the people who are genuinely in need from accessing to the program. Distinguished from the policy study about the affordable housing program, this research is conducted from law perspective to investigate drawbacks in the legal system of affordable housing distribution. Based on the Rawls’ theory of justice and the framework of legal operating system of affordable housing distribution, the researcher conducts investigation from four perspectives, which are affordable housing legislation, enforcement, judiciary and sanction. The aims of this study are to explore the general picture of affordable housing development in Yinchuan; to identify the problem in affordable housing distribution in Yinchuan; to investigate drawbacks in affordable housing distribution system in Yinchuan and to examine views and perceptions of low income respondents upon the affordable housing distribution system in Yinchuan. Data collection techniques involve documents, observation, interview and survey using questionnaire. The questionnaire is designed based on the findings of documents analysis, observation and interview. Data gathered from the survey are analyzed descriptively. The findings reveal that there are some drawbacks in the affordable housing distribution system, which consists of legislation upon eligibility, distribution execution, judiciary and sanction. Each subsystem is not perfect to play its role in safeguarding fair distribution.Legislation upon eligibility criteria and required proof documents are not clear and adequate enough to ensure eligibility of applicants. The execution of distribution consists of four procedures in which each procedure does not function effectively due to its defects. The judiciary consists of three types, which are from civil, criminal and administrative procedures. There are also some drawbacks in the subsystem of sanction as well. The results of this study suggest that drawbacks in each subsystem make its operation very ineffective and prevent the whole system functioning normally. All these drawbacks result in unfairness and injustice in the process of affordable housing distribution.